2017
DOI: 10.1039/c7ta05967a
|View full text |Cite
|
Sign up to set email alerts
|

Elucidating the role of the hole-extracting electrode on the stability and efficiency of inverted CsSnI3/C60perovskite photovoltaics

Abstract: The correlation between the stability of thin films of black (B)-g CsSnI 3 perovskite in ambient air and the choice of supporting substrate is examined for the substrates: (i) soda-lime glass; (ii) indium tin oxide (ITO) glass; (iii) copper iodide (solution processed)/ITO glass; (iv) poly(3,4-ethylenedioxythiophene):poly(styrenesulfonate) (PEDOT:PSS)/ITO glass; (v) and an optically thin (8 nm) gold film electrode. The performance of (ii)-(v) as the hole-extracting electrode in inverted photovoltaic (PV) device… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
56
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 42 publications
(56 citation statements)
references
References 57 publications
0
56
0
Order By: Relevance
“…S2) View Article Online relative intensities of reflections, indeed we have previously shown that B-g CsSnI 3 films deposited in the same way as used in the current study can exhibit substrate specific preferred crystallite orientation. 9 Since the degree of orientation may also conceivably be affected by the compositions of the samples this analysis cannot be quantified.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…S2) View Article Online relative intensities of reflections, indeed we have previously shown that B-g CsSnI 3 films deposited in the same way as used in the current study can exhibit substrate specific preferred crystallite orientation. 9 Since the degree of orientation may also conceivably be affected by the compositions of the samples this analysis cannot be quantified.…”
Section: Resultsmentioning
confidence: 99%
“…We have recently shown that B-g CsSnI 3 PV devices with an inverted planar device architecture exhibit the best efficiently and stability when not using a hole-transport layer. 8,9 For this reason we have used this simplified device architecture as a test bed for these new perovskite materials that are closely related to B-g CsSnI 3 .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations